Changes in anticoagulant prescription patterns over time for patients with atrial fibrillation around the world. Issue 4 (10th July 2021) - Kozieł, Monika; Teutsch, Christine; Bayer, Valentina; Lu, Shihai; Gurusamy, Venkatesh K.; Halperin, Jonathan L.; Rothman, Kenneth J.; Diener, Hans‐Christoph; Ma, Chang‐Sheng; Huisman, Menno V.; Lip, Gregory Y. H.
Abstract: Background: Prescribing patterns for stroke prevention in atrial fibrillation (AF) patients evolved with approval of non‐Vitamin K antagonist oral anticoagulants (NOACs) over time. Objectives: To assess changes in anticoagulant prescription patterns in various geographical regions upon first approval of a NOAC and to analyze the evolution of oral anticoagulants (OACs) use over time in relation to CHA2 DS2 ‐VASc and HAS‐BLED risk profiles. Methods: Global Registry on Long‐Term Oral Antithrombotic Treatment in Patients with Atrial Fibrillation ( GLORIA‐AF) Phases II and III reported data on antithrombotic therapy for patients with newly diagnosed AF and ≥1 stroke risk factor. We focused on sites enrolling patients in both phases and reported treatment patterns for the first 4 years after initial NOAC approval. Results: From GLORIA‐AF Phases II and III, 27 432 patients were eligible for this analysis. When contrasting the first year with the fourth year of enrolment, the proportion of NOAC prescriptions increased in Asia from 29.2% to 60.8%, in Europe from 53.4% to 75.8%, in North America from 49.0% to 73.9% and in Latin America from 55.7% to 71.1%. The proportion of Vitamin K antagonists (VKAs) use decreased across all regions over time, in Asia from 26.0% to 9.8%, in Europe from 35.5% to 16.8%, in North America from 28.9% to 12.1%, and in Latin America from 32.4% to 17.8%. In the multivariable analysis, factors associated with NOAC prescription were as follows: enrolment year, type of site, region, stroke and bleeding risk scores, and type and categorization of AF. Conclusions: During 4 years after the approval of the first NOAC, NOAC use increased, while VKA use decreased, across all regions. Abstract : Treatment patterns for stroke prevention in AF overtime were assessed globally. The novelty of this study refers to evaluation of changes upon first approval of a NOAC. NOAC use increased and VKA use decreased over 4 years.